Penang Bridge Marathon 17 December 2023 / Assoc Prof Dr Hoe Foo Terng - Hoe, Foo Terng (Academy of Language Studies, 2024)
The number of people who signed up for the 2023 Penang Bridge Marathon was 25,000. The bridge run was divided into threecategories: marathon, half marathon and 10km Fun Run. The full marathon category was divided into four groups: men's open (with the running numbers starting with A), women's open (with the running numbers starting with B), men's veteran (with the running numbers starting with C) and women's veteran (with the running numbers starting with D). The half marathon category was also divided into 4 groups, but the running numbers were preceded by E, F, G, and H. The 4 groups of the 10km Fun Run were the men’s open (the running number was preceded by J), the women’s open (the running number was preceded by K), the male junior (the running number was preceded by M), and the female junior (the running number was preceded by N). In this Bridge Marathon, I was a referee for the men's veteran group (full marathon) and the female junior group of the 10km Fun Run. With the use of electronic timing, the records of the run were captured without any glitches. The full marathon was flagged-off by the representative of the Chief Minister of Penang at 1:30 am, while the half marathon was flagged-off at 3 am. Both starting and finishing points were at the Queensbay Mall car park. The 10km Fun Run started at the Eastin Hotel at 6:30 in the morning and ended at the same place as the half marathon. The award presentation ceremony was held at 8:00 in the morning, and the whole event went on smoothly without any complaints.